Routledge handbook on South Asian foreign policy - Pande, Aparna (Routledge/Taylor & Francis Group, 2021)
"This handbook offers a comprehensive overview of South Asian foreign policy, examining the complex history and present state of South Asian foreign policy, the foreign policy of the countries of the region as well as their relationships with their neighbors and key external players, such as China and the U.S., in an effort to understand South Asia's place in the world order. It illustrates the future trajectory of foreign policy in the region and analyses future of regional arrangements like SAARC (South Asian Association for Regional Cooperation) and BIMSTEC. The handbook is structured in five parts, each representing a focused area of enquiry: Foreign Policy Relations within South Asia Relations within Indo-Pacific Relations with China, Europe and U.S. Security A carefully selected collection of 27 chapters written by experts on South Asian foreign, economic and security policy, this handbook provides an objective yet accessible overview of the history and current state of foreign policy of each country and the region. It is an authoritative reference work for academics and students as well as international think tanks, research institutes, and non-governmental organizations working on South Asian Politics, Asian Politics, Foreign Politics, International Affairs, World History, and International Relations"--